The Collapse of Meaning in McCarthy’s The Road: A Post-Modern Critique - Saleem, Javeria; Waheed, Sadia; Khan, Ayesha (Annals of Human and Social Sciences, 2025)
This study analyzes Cormac McCarthy’s The Road (2022) from the Postmodernist-Marxist theoretical framework of Fredric Jameson, which he cited in his book Postmodernism, or The Cultural Logic of Late Capitalism (1991), and aims to uncover how the characters, dialogues, and incidents reflect meaninglessness, fragmentation, and superficiality. Moreover, this study critically examines how capitalism shapes the economic world and prophesizes how it could lead humans to self-destruction. The Road (2022) is a narrative about two characters, ‘the boy’ and ‘the man,’ trying to construct the meaning of their identities and surroundings while trying to survive in a post-apocalyptic world. This post-modern critique traces these phenomena in the narrative through close reading and thematic analysis. The present study concludes that the erosion of meaning and identity foreshadows the disastrous effects of late capitalism and suggests that readers reflect on their cultural and environmental practices in a deeper insight and consider the hazardous effects of late capitalism.